Deceptive Identity Performance: Offender Moves and Multiple Identities in Online Child Abuse Conversations. (23rd March 2018) - Chiang, Emily; Grant, Tim
Abstract: This article provides a case study of deceptive online identity performance by a convicted child sex offender. Most prior linguistic and psychological research into online sexual abuse analyses transcripts involving adult decoys posing as children. In contrast, our data comprise genuine online conversations between the offender and 20 victims. Using move analysis (Swales 1981, 1990), we explore the offender's numerous presented personas. The offender's use of rhetorical moves is investigated, as is the extent to which the frequency and structure of these moves contribute to and discriminate between the various online personas he adopts. We find from eight frequently adopted personas that two divergent identity positions emerge: the sexual pursuer/aggressor, performed by the majority of his online personas, and the friend/boyfriend, performed by a single persona. Analysis of the offender's self-describing assertives suggests this distinctive persona shares most attributes with the offender's 'home identity'. This article importantly raises the question of whether move analysis might be useful in identifying the 'offline persona' in cases where offenders are known to operate multiple online personas in the pursuit of child victims.